The Main Trends in the Development of Corporate Governance Through the Prism of Domestic and Foreign Experience - Zh. A. Bekpayeva; N. V. Nikiforova; M. A. Karlik (Экономика: стратегия и практика, 2022)
The prerequisite for studying the topic was that the topic of corporate governance is relevant, especially in our turbulent, unstable times. This is confirmed by the interest shown by authors from various countries. In the literature review subsection, articles on corporate governance by various authors from the Scopus database were studied. From the point of view of the authors, the activity of any organization depends on many different external and internal factors, such as the competence of management, the qualifications of employees, the availability of financial and labor resources for business development.   Through the application of the methodology and methods of classical science, the goals of writing the article are revealed: the article presents a concise history of the development of corporate governance in the international and domestic markets in a convenient form, identifies the main three theories of corporate governance, and identifies differences in the codes of various countries in tabular form. The article confirms the information that underestimation of the importance of corporate governance can lead to several losses in the company, the impossibility of implementing the strategy, and inefficient use of resources: material, intellectual, labor, and financial. An assessment of the positive impact of the corporate management system as a whole on the company’s efficiency is given. The results of the study can be applied in building a corporate management system for companies, regardless of the form of ownership and the number of employees. The topic of corporate governance is especially relevant in the current realities.